2012
DOI: 10.1177/0883073811435238
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Infantile De Novo Primary Antiphospholipid Syndrome Revealed by a Neonatal Arterial Ischemic Stroke

Abstract: The few cases of antiphospholipid syndrome that have been reported in neonates are believed to have resulted from a transplacental transfer of antiphospholipid antibodies. Here we report on a boy with a neonatal stroke revealing a de novo primary antiphospholipid, the mother being free of antiphospholipid antibodies. Other thrombosis risk factors included primiparity, gestational diabetes, macrosomia, polyglobulia, and lipoprotein(a) >30 mg/dL. Anti-cardiolipin and anti-β(2)-glycoprotein I persisted more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…For example, in one case of a 3-day old infant with perinatal ischemic stroke, aCL was detected at high titers. 57 However, the infant did not experience thrombotic recurrence thereafter.…”
Section: Anticardiolipin Antibodymentioning
confidence: 86%
See 1 more Smart Citation
“…For example, in one case of a 3-day old infant with perinatal ischemic stroke, aCL was detected at high titers. 57 However, the infant did not experience thrombotic recurrence thereafter.…”
Section: Anticardiolipin Antibodymentioning
confidence: 86%
“…So far, few studies have assessed the impact of long term anticoagulation or antiplatelet on the risk of cerebral arterial thrombosis complications and recurrence. While the use of aspirin can lead to the prevention of recurrent events and a neurological recovery in some patients, 57 other patients with same type of aPL positivity had recurrence and neurological deficits on follow-up. 13 Based on few case reports, neonates who used low-molecular-weight heparin (LMWH) in combination with aspirin did not have neurological complications upon follow-up.…”
Section: Managementmentioning
confidence: 99%
“…At the present time, it is still unclear whether outcomes for de novo and transmitted neonatal APS are different, and whether the de novo APS may precede other autoimmune diseases, such as systemic lupus erythematosus (26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that 43% of the patients in this study had seizures as a major clinical manifestation and that these were usually secondary to cerebral artery infarcts. Thus, epilepsy development was unusual [10, 11, 1417, 20, 21]. Alshekaili et al [17] described the case of a 5-day-old newborn who had a reduction in spontaneous right limb movements.…”
Section: Discussionmentioning
confidence: 99%